2011
DOI: 10.1111/j.1528-1167.2011.03348.x
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency stimulation of ventral hippocampal commissures reduces seizures in a rat model of chronic temporal lobe epilepsy

Abstract: SUMMARY Purpose To investigate the effects of low frequency stimulation (LFS) of a fiber track for the suppression of spontaneous seizures described by Nissinen in a rat model of human temporal lobe epilepsy. Methods Stimulation electrodes were implanted into the ventral hippocampal commissure (VHC) in a rat post-status epilepticus (SE) model of human temporal lobe epilepsy (n = 7). Two recordings electrodes were placed in the CA3 regions bilaterally and neural data was recorded for a minimum of six weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 65 publications
(76 reference statements)
2
56
0
Order By: Relevance
“…This was in accordance with a previous study on high frequency hippocampal DBS in the KA rat model [3]. This observation is in contrast with the clear outlasting effects of two weeks low frequency DBS of the ventral hippocampal commissure in the amygdala stimulation post SE rat model [30]. Immediate increases in seizure rate after hippocampal DBS discontinuation has been reported in patients [13,16].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This was in accordance with a previous study on high frequency hippocampal DBS in the KA rat model [3]. This observation is in contrast with the clear outlasting effects of two weeks low frequency DBS of the ventral hippocampal commissure in the amygdala stimulation post SE rat model [30]. Immediate increases in seizure rate after hippocampal DBS discontinuation has been reported in patients [13,16].…”
Section: Discussionsupporting
confidence: 85%
“…During bilateral hippocampal DBS the mean decrease in electrographic seizure rate compared to baseline was 45%, whereas this reduction was only 14% during unilateral hippocampal DBS. Previous studies on the effect of DBS in one region of the hippocampal formation on spontaneous seizures reported a reduction in mean seizure rate ranging from no reduction in seizure rate [23] to 90% reduction in seizure rate [30]. A previous trial in the same animal model with identical stimulation parameters to our unilateral hippocampal DBS paradigm, except for the stimulation intensity, reported a mean reduction in seizure rate of 26%.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrasting experiments, responsive pulse stimulation at 5 Hz was reported to stop seizure activity in the kainate rat model more effectively than 60 and 130 Hz (Rajdev et al 2011). In support of ongoing studies on the development of low-frequency hippocampal stimulation as a novel option for the treatment of MTLE (see also Kile et al 2010;Rashid et al 2012), we suggest that optimization of the frequency of applied stimulation, along with other important parameters, which include the waveform shape and the amplitude of the stimulation, the anatomical areas targeted and the activity status, as well as the resonant oscillatory frequency of the targeted cells, might critically contribute to predict neurobiological responses in vivo and to guide the selection of stimulation parameters in further applications.…”
Section: Discussionmentioning
confidence: 99%
“…From an electrophysiological standpoint, previous studies in hippocampal slice preparations indicated that exogenous, lowfrequency, sinusoidal fields may mimic the action of endogenous oscillations in LFPs by causing subthreshold shifts to the somato-dendritic polarization of the cell membrane, which influences the synchronicity of firing in the targeted neuronal populations (Jefferys 1981;Radman et al 2007;Reato et al 2010;Terzoulo and Bullock 1956). Moreover, direct excitation delivered to axons could pace efferent output and/or antidromic stimulation to distant projections, even in the absence of local somatic/perisomatic activation (Li et al 2007;McIntyre et al 2004aMcIntyre et al , 2004b; see also Gradinaru et al 2009).…”
Section: Discussionmentioning
confidence: 99%